Modeling of Gross Domestic Product Growth in Indonesia by Using Multi-Input Intervention Model - Chandrawati, Chandrawati; Kertanah, Kertanah; Ramli, Tri Juliantin; Chintyana, Alissa; Hirzi, Ristu Haiban (Universitas Negeri Gorontalo, 2024)
The Gross Domestic Product (GDP) Growth of Indonesia has fluctuated over time due to established policies, economic crises, changes in political direction, and natural disasters. In 1998, due to the fall of the New Order regime, the Indonesian economy contracted by -13.13 percent, leading to hyperinflation. In 2020 the COVID-19 pandemic occurred which caused Indonesia's GDP Growth to contract again. Accurate forecasting of GDP Growth is crucial for government to formulate effective future policy strategies to maintain the stability of Indonesia's economy. There are several outliers in Indonesia's GDP Growth data, so the proper analysis is a multi-input intervention. The best model analysis is ARIMA (1,0,0) with non-zero mean using the first order intervention b=0, r=0, s=0 and the second order intervention b=0, r=0, and s=0 which resulted in a Mean Absolute Percentage Error (MAPE) of 23.47 percent. The outlier effect on Indonesia's GDP Growth data is both direct and temporary.